Ajaran Brahmawidya Dalam Lontar Eka Pratama - I Wayan Titra Gunawijaya; Ni Kadek Sri Andayani (Jnanasiddhanta : Jurnal Teologi Hindu, 2022)
Lontar Eka Prathama considers marriage to be a ceremony that must be carried out with a sacred ceremonial order, because marriage according to the teachings of Hinduism is yajna, so that people who enter the marriage bond will go to the gate of the grahasta hostel to better understand the concept of marriage from various aspects. Through this, we will examine the problems regarding the teachings of the Brahmawidya contained in eka pratama ejection. The method used in this study is a qualitative method with data sources in the form of primary data and secondary data, through data collection techniques including observation techniques, interviews, literature and documentation, as well as techniques for determining informants which are then processed and presented descriptively. The results of the study show that the existence of eka pratama lontar as a source of teachings is related to the implementation of the manusa yajna ritual. The meaning of the divine teachings is the worship of God's manifestation in the form of a god in the form of offerings as a means of worship or the embodiment of God/Gods in the form/form of offerings with various symbols. The discussion on the concept of chastity in eka pratama ejection states how sacred the wedding ceremony is in the series of humanusyadnya ceremonies that will be carried out. In addition to the concepts of brahmawidya and holiness, it is also discussed about the harmony that will be established according to the Lontar Eka Pratama concept, namely the harmony of relations in the household according to the obligations of the husband or wife.